Rancang Bangun Alat Fetal Doppler Berbasis IoT - Romi Mulyadi; Albirruni Siregar; Muhammad Ikhwanul Ikhsan; Abu Bakar; Yona Ramadhika (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
This research is motivated by the phenomenon of slowing population growth due to decreased birth rates caused by several factors, especially the risks caused by the distance that must be traveled between homes and hospitals, besides that there are various diseases that cause the fetus to not be delivered successfully. Thus, a tool is needed to facilitate and reduce the risks that have been mentioned. This design was made based on the plan in the process and workings of this IoT-based fetal doppler device and in knowing the normal or abnormal fetal heart rate. In this study the development method was used, which in this method is more focused, in developing goals, expanding, and digging deeper until the desired goals are obtained. The first step is to collect data, search and study data and theories related to the IoT-based fetal Doppler device design system. 2.5 MHz frequency transducer that sends and receives reflections generated from objects. This reflection turns into an electric current which is amplified and filtered by the transducer. Furthermore, the electricity is amplified by the amplifier until DJJ's voice is heard from the speakers. The transducer circuit processes the signal received at the amplifier until the data obtained is sent and processed by NodeMCU. After processing, NodeMCU gets fetal heart rate data on Display and Thingspeak. The results of this study were obtained from survey results, users with questionnaire respondents as many as 40 samples were calculated using a Likert scale. Users agree that the tool is able to provide ease of use with a score of simplicity of 4.94%, interactivity of 4.30% and usability of 3.39% on a scale of 5. And the design of the tool can reduce the risk of possible acquisition, as well as make it easier for some parties.